"Neptune to the Common-wealth of England" (1652): the "Republican Britannia" and the continuity of interests. Issue 4 (8th August 2018) - Maley, Willy
ABSTRACT: In the seventeenth century, John Kerrigan reminds us, "models of empire did not always turn on monarchy". In this essay, I trace a vision of "Neptune's empire" shared by royalists and republicans, binding English national interest to British overseas expansion. I take as my text a poem entitled "Neptune to the Common-wealth of England", prefixed to Marchamont Nedham's 1652 English translation of Mare Clausum (1635), John Selden's response to Mare Liberum (1609) by Hugo Grotius. This minor work is read alongside some equally obscure and more familiar texts in order to point up the ways in which it speaks to persistent cultural and political interests. I trace the afterlife of this verse, its critical reception and its unique status as a fragment that exemplifies the crossover between colonial republic and imperial monarchy at a crucial moment in British history, a moment that, with Brexit, remains resonant.